Tessitura da inclusão na Universidade Federal de Sergipe : múltiplos olhares - Cruz, Cândida Luisa Pinto (2016)
This research aimed to know the construction of the first initiatives for inclusion of people with disabilities in the Federal University of Sergipe (FUS). The aim was to understand the process of inclusion of students with disabilities in the FUS under an approach of the participants of this process: teachers, students with and without disabilities and caregivers. In this sense, a building was necessary to guide and interweaves the facts. In this perspective, the agreement between the government of the State of Sergipe and the State Department of Education with the Cuban government was revealed, as well as the Department of Education of the FUS, focusing on scientific actions for the training of teachers and technicians from state networks and federal to meet people with disabilities in various educational stages. The methodological procedure adopted was the case study, a research approach qualitativa.Os instruments for data collection were semi-structured interviews with 22 subjects interviewed. It was defined as the search location the Center for Education and Human Sciences-CEHS / FUS, Campus São Cristovão. The results show that the CEHS started the discipline of inclusion focused on the subject in the Department of Psychology, but the Department of Education began the process of forming professional teachers; in an inclusive perspective, to work in the private and public networks of the State of Sergipe.